Evaluation of global DNA methylation, homocysteine and vitamin B12 levels among patients with celiac disease - Farah Tareq Yaseen; Rakad M.Kh. Al-Jumaily (Gastroenterologìa)
Celiac disease (CD) is an immune-mediated disorder caused by gluten in genetically susceptible individuals characterized by chronic inflammation that essentially affects the small intestine. Objective: this study was designed to measure the potential role of some serological biomarkers including vitamin B12 and homocysteine (HCY) in the progression of CD as well as their relations to global DNA methylation (5mC). Materials and methods. Forty CD patients were enrolled in the study with an average age of (36.60 ± 2.03) years (range between 15 and 60). The diagnosis of the disease was confirmed by serological examinations and intestinal endoscopy in Gastroenterology and Liver Teaching Hospital in the Medical City Hospital in Baghdad city. Also, 40 healthy subjects were included in this study as control group with an average age of (32.22 ± 1.97) years (range between 16 and 59). The blood serum was checked for serological biomarker levels using an enzyme-linked immunosorbent assay. Also, DNA extracted from whole blood and the levels of 5mC were evaluated. Results. The analysis of serological biomarker data has shown that the mean vitamin B12 significantly decreases in CD patients compared to healthy controls: (109.80 ± 2.53) and (143.65 ± 2.36) pg/ml. Also, the results demonstrated a significant increase in HCY in CD patients compared to healthy controls — (10.60 ± 0.41) and (3.92 ± 0.23) umol. The results of global DNA methylation showed a highly significant decrease (P ≤ 0.01) in blood samples of patients with celiac disease (0.435 ± 0.020) vs. controls (0.594 ± 0.040). Conclusions. The findings of this study suggest that the differences in global DNA methylation levels may be used as a risk factor for developing CD, which indicates the involvement of vitamin B12 and HCY in CD progression.